2023
DOI: 10.1007/s12672-023-00813-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis, mechanism and therapy of Cav1 in prostate cancer

Qiang Bian,
Bei Li,
Luting Zhang
et al.

Abstract: Prostate cancer is the second incidence of malignant tumors in men worldwide. Its incidence and mortality are increasing year by year. Enhanced expression of Cav1 in prostate cancer has been linked to both proliferation and metastasis of cancer cells, influencing disease progression. Dysregulation of the Cav1 gene shows a notable association with prostate cancer. Nevertheless, there is no systematic review to report about molecular signal mechanism of Cav1 and drug treatment in prostate cancer. This article re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 121 publications
1
1
0
Order By: Relevance
“…Abnormal Cav1 expression leads to faster progression of prostate cancer and is not conducive to treatment. [27] The above literature review is consistent with our results, and based on above literature analysis, we speculate that CAV1 may play an important role in occurrence and development of prostate cancer, but its mechanism of action on prostate cancer needs to be further explored.…”
Section: Discussionsupporting
confidence: 90%
“…Abnormal Cav1 expression leads to faster progression of prostate cancer and is not conducive to treatment. [27] The above literature review is consistent with our results, and based on above literature analysis, we speculate that CAV1 may play an important role in occurrence and development of prostate cancer, but its mechanism of action on prostate cancer needs to be further explored.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the silencing of MCT-4 impaired the maturation and trafficking of CD147 to the cell surface, resulting in the accumulation of CD147 in the endoplasmic reticulum [49]. Recent studies revealed the involvement of CD147 in cancer cell glycolysis in various malignant tumors including non-small-cell lung cancer, hepatocellular carcinoma, colorectal cancer, prostate cancer, and anaplastic large-cell lymphoma [50][51][52][53][54][55]. These findings strongly suggest that CD147 interacts with MCT-1 and MCT-4 to promote glycolysis in tumor cells, resulting in tumor progression (Figure 2).…”
Section: Cd147 In Cancer Cell Glycolysismentioning
confidence: 99%